2019
DOI: 10.1101/532309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Streptomycesendophytes promote the growth ofArabidopsis thaliana

Abstract: 19 20 21 22 23 101 10% (v/v) glycerol and serial dilutions were spread onto either soya flour mannitol (SFM) agar, 102 starch casein agar, or minimal medium agar containing sodium citrate (Lebeis et al 2015).103Plates were incubated at 30C for up to 14 days. Colonies resembling streptomycetes were re-104 streaked onto SFM agar and identified by 16S rRNA gene PCR amplification and sequencing 105 with universal primers PRK341F and MPRK806R (see Table S1 for primers, plasmids and 106 strains used in this work). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 108 publications
(96 reference statements)
1
17
0
Order By: Relevance
“…The previously reported fertilizing effect of REEs on different food crops could hence be partially the result of increased competitiveness of plant growth promoting organisms such as P. putida during root colonization. This hypothesis is further supported by a recent study, which found that Pseudomonads predominantly thrive on root exudates in vivo and are hence enriched in the rhizosphere of Arabidopsis thaliana (10). As such, it will be interesting to see what future research will add to the currently emerging theme of REEs being an important micronutrient for methylotrophic and non-methylotrophic organisms.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The previously reported fertilizing effect of REEs on different food crops could hence be partially the result of increased competitiveness of plant growth promoting organisms such as P. putida during root colonization. This hypothesis is further supported by a recent study, which found that Pseudomonads predominantly thrive on root exudates in vivo and are hence enriched in the rhizosphere of Arabidopsis thaliana (10). As such, it will be interesting to see what future research will add to the currently emerging theme of REEs being an important micronutrient for methylotrophic and non-methylotrophic organisms.…”
Section: Discussionsupporting
confidence: 58%
“…Its diversity is mainly shaped by root exudates, a complex mixture of organic compounds including carbohydrates, amino acids, or carbon acids (4, 5) and plant-, fungal-, and bacteria-derived volatiles (VOCs) such as alkenes, alcohols, terpenes or benzenoids (6, 7). As such, it is not surprising that the soil-dwelling organism P. putida KT2440 is equipped with a broad diversity of metabolic pathways in order to maximize its cellular fitness in different environmental niches including the rhizosphere (810). For efficient growth on various alcoholic VOC substrates, it uses a periplasmic oxidation system consisting of the pyrroloquinoline quinone-dependent alcohol dehydrogenases (PQQ-ADHs) PedE and PedH (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the previously reported fertilizing effect of REEs on different food crops (34)(35)(36)(37)(38) could be a consequence of increased competitiveness of plant growth-promoting organisms such as P. putida during root colonization. This hypothesis is supported by a recent study which found that pseudomonads thrive predominantly on root exudates in vivo and are hence enriched in the rhizosphere of Arabidopsis thaliana (10). As such, it will be interesting to see what future research will add to the currently emerging theme of REEs being important micronutrients for methylotrophic and nonmethylotrophic organisms, in particular in regard to bacterium-plant interactions.…”
Section: Discussionmentioning
confidence: 71%
“…Its diversity is predominantly shaped by root exudates, a complex mixture of organic compounds, including carbohydrates, amino acids, or carbon acids (4,5) and plant-, fungus-, and bacterium-derived volatiles (VOCs) such as alkenes, alcohols, terpenes, or benzenoids (6,7). As such, it is not surprising that the soil-dwelling organism Pseudomonas putida KT2440 is equipped with a broad diversity of metabolic pathways to maximize its cellular fitness in different environmental niches (8)(9)(10). For efficient growth on various alcoholic VOC substrates, P. putida uses a periplasmic oxidation system consisting of the pyrroloquinoline quinone-dependent alcohol dehydrogenases (PQQ-ADHs) PedE and PedH.…”
mentioning
confidence: 99%
“…440 million years ago shortly after plants began to colonize land and it has been suggested that their filamentous growth and diverse secondary metabolism may have evolved to enhance their ability to colonize plant roots ( Chater, 2016 ). Several studies have reported that streptomycetes are abundant inside the roots of the model plant Arabidopsis thaliana ( Bulgarelli et al, 2012 ; Lundberg et al, 2012 ; Schlaeppi et al, 2014 ; Bai et al, 2015 ; Carvalhais et al, 2015 ) where they can have beneficial effects on growth ( Worsley et al, 2020 ) while others have shown that streptomycetes can protect crop plants such as strawberry, lettuce, rice and wheat against biotic and abiotic stressors, including drought, salt stress, and pathogenic infection ( Viaene et al, 2016 ; Newitt et al, 2019 ). However, different plant genotypes are associated with distinctive root-associated microbial communities and not all plant species enrich streptomycetes in their roots, a notable example being barley ( Bulgarelli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%